INFLUENCE OF THE USE OF ZEOLITE POWDER AND KINANG JINGKION POWDER AS A SUBSTITUTE FOR FILLER AGAINST HOT ASPHALT MIXTURE (HRS – WC) - Sihaloho, Roy Chandra; Bahtiar, Bahtiar; Rante, Harmonis (INFOKUM, 2022)
Highways in Indonesia generally use this type of bending pavement. To get a good bending pavement, it is necessary to plan a good asphalt mixture. One type of bending pavement is Hot Rolled Sheet (HRS). The use of cement and stone ash in asphalt mixtures results in an increasingly expensive price. It is necessary to innovate to try to replace cement and stone ash with other materials. Alternatives to the filler substitute are zeolite powder and Kinang Jingkion Powder. The purpose of this study is to determine and analyze the effect of using zeolite powder and Kinang Jingkion Powder as filler on HRS-WC hot asphalt mixture. This research was conducted by making a mixture of HRS-WC hot asphalt by using zeolite powder and Kinang Jingkion Powder as fillers with variations in asphalt content of 5.5%, 6.0%, 6.5%, 7.0% and 7.5% As a comparison, test objects with cement as filler were also made. Marshall Test results on Optimum Asphalt (KAO) 6.975% for Cement fillers received a stability value of 1242.90 Kg, MQ of 396.9 Kg / mm, VIM of 2.70% and VFB of 81.30%. Zeolite filler with KAO 7.04% received a stability value of 1335.8 Kg, MQ of 422.5 Kg/mm, VIM of 2.31% and VFB of 82.64%. Meanwhile, the Kinang Jingkion Filer with a KAO of 6.85% got a stability value of 1194.40 Kg, MQ of 460.2 Kg / mm, VIM of 2.68% and VFB of 80.16%.